IMPLEMENTASI INOVASI DIGITAL LEARNING HUB UNTUK MENINGKATKAN KEMAMPUAN BELAJAR INFORMATIKA PADA KELAS XII SMAN 1 KEDUNGWUNI PEKALONGAN - Siti Rosmalina Edelwis; Beni Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology necessitates innovation in school management and instructional practices, particularly in Informatics subjects that emphasize computational thinking skills. This study aims to analyze the implementation of a Canva Web–based Digital Learning Hub and the influence of digital-based school management innovation on improving the Informatics learning abilities of Grade XII students at SMA Negeri 1 Kedungwuni Pekalongan. This research employed a mixed-methods approach with a One Group Pretest–Posttest design, involving 72 students as research participants. Data were collected through tests, questionnaires, interviews, and documentation, and were analyzed using descriptive statistics and a Paired Sample t-Test with the assistance of SPSS. The results indicate an increase in students’ mean scores from 89.58 in the pretest to 95.35 in the posttest, with a significance value of 0.000 (p < 0.05),demonstrating a statistically significant improvement in learning outcomes. Furthermore, the Digital Learning Hub effectively supports computational thinking–based Informatics learning through structured content delivery, interactive exercises, Python programming practice, and context-based projects aligned with the Adiwiyata program. These findings suggest that digital-based school management innovation through the implementation of a Digital Learning Hub is effective in enhancing students’ Informatics learning abilities and supporting sustainable instructional quality.